The Role of Kartika Eka Paksi's Doctrine in Supporting The Realization of Strengthening The National Defense Strategy in The Perspective of 5 Functions - Achdwiyanto Yudi Hartono; Zainal Arifin; Sutanto Sutanto (Green Publisher Indonesia, 2025)
This research examines the limitations of Indonesia's defense strategy, focusing on the Indonesian Army Aviation Corps (Puspenerbad) and its underutilized potential in national defense. Despite the Indonesian National Army's critical role in safeguarding the nation’s sovereignty, the current defense policies are fragmented and primarily emphasize core defense components, leaving aviation support functions insufficiently integrated. The study uses a qualitative approach, gathering data from journals, books, and official documents to analyze Puspenerbad’s five key functions: combat intelligence, maneuver, fire support, protection, and logistical assistance. The findings suggest that optimizing these functions could significantly enhance Indonesia's defense capabilities in addressing both military and non-military threats. The research highlights the need for a more comprehensive defense strategy, proposing that an improved aviation corps could strengthen national security by better integrating aviation support into the broader defense framework. This study offers valuable insights for policymakers and military planners, aiming to improve operational effectiveness and better prepare Indonesia for emerging security challenges